Supply Chain Management Performance of the Furniture Industry in Ambon during the Covid-19 Pandemic - Fransiska Natalia Ralahallo; Edward Gland Tetelepta; Asiani Sijabat (Budapest International Research and Critics University, 2022)
Supply Chain Management (SCM) is implemented within a company with the objective of improving operational performance, in order to create a competitive advantage. Information sharing, long term relationship, cooperation and process integration are important elements in Supply Chain Management, which function to accelerate supply chain processes from suppliers to the markets or to the consumers. This research is conducted on the furniture industry in the city of Ambon. The problems that are often encountered by the furniture industry are typical problems such as, lack of capital and limited access to raw materials, especially seasonal ones. In addition, there is also the problem of partnership, which is triggered by the difficulty of integrating farmers (raw material suppliers) and raw material processing companies into a solid partnership, due to differences in interests. The purpose of this research is to analyze the influence of information sharing, long term relationship, cooperation, and process integration towards supply chain management performance within the company. The result of the research is (1) the information sharing variable has a significant influence towards supply chain management performance; (2) long-term relationship variable has no significant influence towards supply chain management performance; (3) the cooperation variable has a significant influence towards supply chain management performance and; (4) the integration process variable has a significant influence towards supply chain management performance